Production of hydrogen peroxide by alveolar macrophages from rats exposed to subacute and chronic hypoxia - Wilhelm, J; Sojková, J; Herget, J (Physiological research, 1996)
We have studied in vitro alveolar macrophages (AMs) obtained by tracheobronchial lavage from rats exposed to subacute (3 hours and 3 days) and chronic (3 weeks) hypoxia (FiO2 = 0.1) and from rats recovering from chronic hypoxia. Hydrogen peroxide production by AMs was measured by luminol-dependent chemiluminescence after AMs adhered to the walls of the measuring cuvette, after stimulation with phorbol-myristate-acetate (PMA), and when N-formyl-methionyl-leucyl-phenylanine (FMLP) was added subsequently to the cells which had been previously stimulated by adherence or PMA. H2O2 production after cell adherence and adherence combined with FMLP stimulation did not differ between the groups. The increase of H2O2 production after adding PMA, and FMLP in addition to PMA was significantly higher in AMs from rats exposed to hypoxia for 3 days than in the controls. Other experimental groups did not differ from their controls. It is concluded that 3 days' hypoxia primes AMs for enhanced production of H2O2 upon stimulation. The mechanism is probably at the level of synthesis of proteins involved in H2O2 production, or the shift to a more reactive phenotype of alveolar macrophages subpopulations.
Keywords: tetradekanoylforbolacetát; Male; Tetradecanoylphorbol Acetate; luminiscenční měření; Rats, Wistar; reaktivní formy kyslíku; N-formylmethionin-leucyl-fenylalanin; hypoxie; Hypoxia; N-Formylmethionine Leucyl-Phenylalanine; peroxid vodíku; mužské pohlaví; potkani Wistar; alveolární makrofágy; Hydrogen Peroxide; buněčná adheze; krysa rodu Rattus; Reactive Oxygen Species; Animals; zvířata; Rats; Macrophages, Alveolar; Luminescent Measurements; Cell Adhesion